Predictive Effect of Well-Known Risk Factors and Foot-Core Training in Lower Limb Running-Related Injuries in Recreational Runners: A Secondary Analysis of a Randomized Controlled Trial. Issue 1 (January 2022) - Suda, Eneida Yuri; Watari, Ricky; Matias, Alessandra B.; Taddei, Ulisses T.; Sacco, Isabel C.N.
Background: Running carries the risk of several types of running-related injuries (RRIs), especially in the lower limbs. The variety of risk factors and the lack of strong evidence for several of these injury risks hinder the ability to draw assertive conclusions about them, hampering the implementation of effective preventive strategies. Because the etiology of RRIs seems to be multifactorial, the presence of RRI risk factors might influence the outcome of therapeutic strategies in different ways. Thus, further investigations on how risk and protective factors influence the incidence and prevention of RRIs should be conducted. Purpose: To investigate the predictive effect of well-known risk factors and 1 protective factor—foot-core training—on the incidence of lower limb RRIs in recreational runners. Study Design: Cohort study; Level of evidence, 2. Methods: Middle- and long-distance recreational runners (N = 118) were assessed at baseline and randomly allocated to either an intervention group (n = 57) or a control group (n = 61). The intervention group underwent an 8-week (3 times/wk) foot-core training program. Participants were followed for a year after baseline assessment for the occurrence of RRIs. Logistic regression with backward elimination of variables was used to develop a model for prediction of RRI in recreational runners. Candidate predictor variables included age, sex, body mass index, years of running practice, number of races, training volume, training frequency, previous RRI, and the foot-core exercise training. Results: The final logistic regression model included 3 variables. As previously shown, the foot-core exercise program is a protective factor for RRIs (odds ratio, 0.40; 95% CI, 0.15-0.98). In addition, older age (odds ratio, 1.07; 95% CI, 1.00-1.14) and higher training volume (odds ratio, 1.02; 95% CI, 1.00-1.03) were risk factors for RRIs. Conclusion: The foot-core training was identified as a protective effect against lower limb RRI, which can be negatively influenced by older age and higher weekly training volume. The predictive model showed that RRIs should be considered a multivariate entity owing to the interaction among several factors. Registration: NCT02306148 (ClinicalTrials.gov identifier).